Lactic acid bacteria in the prevention of pneumococcal respiratory infection: Future opportunities and challenges - Villena, Julio Cesar (2011)
Lactic acid bacteria (LAB) are technologically and commercially important and have various beneficial effects on human health. Several studies have demonstrated that certain LAB strains can exert their beneficial effect on the host through their immunomudulatory activity. Although most research concerning LAB-mediated enhanced immune protection is focused on gastrointestinal tract pathogens, recent studies have centered on whether these immunobiotics might sufficiently stimulate the common mucosal immune system to provide protection to other mucosal sites as well. In this sense, LAB have been used for the development of probiotic foods with the ability to stimulate respiratory immunity, which would increase resistance to infections, even in immunocompromised hosts. On the other hand, the advances in the molecular biology of LAB have enabled the development of recombinant strains expressing antigens from respiratory pathogens that have proved effective to induce protective immunity. In this review we examine the current scientific literature concerning the use of LAB strains to prevent respiratory infections. In particular, we have focused on the works that deal with the capacity of probiotic and recombinant LAB to improve the immune response against Streptococcus pneumoniae. Research from the last decade demonstrates that LAB represent a promising resource for the development of prevention strategies against respiratory infections that could be effective tools for medical application.